Okul öncesi çocuklarının etkileşimli oyun davranışları ile benlik algıları arasındaki ilişkinin incelenmesi - Atıcı, Nevra (My University, 2024)
Bu araştırmanın amacı okul öncesi eğitim kurumuna devam eden 48-72 aylık çocukların sahip oldukları benlik algıları ile etkileşimli oyun davranışları arasındaki ilişkiyi çeşitli değişkenlere göre incelemektir. Araştırma ilişkisel tarama modeline göre planlanmış ve yürütülmüştür. Araştırmanın çalışma grubunu Gaziantep ili merkez ilçelerinde MEB’e bağlı okul öncesi eğitim kurumlarına devam eden ve tesadüfi örneklem yöntemiyle seçilen 48-72 aylık toplam 300 çocuk oluşturmaktadır. Araştırmanın verileri; demografik bilgileri içeren kişisel bilgi formu, Dr. Donald DeMoulin tarafından 1995-1998 yıllarında geliştirilen, Zembat ve arkadaşları tarafından Türkçe’ye çevrilerek (2016) geçerlilik ve güvenilirliği yapılmış olan “Demoulin Çocuklar İçin Benlik Algısı Ölçeği” ile Fantuzzo, Mendez ve Tighe (1998) tarafından erken çocukluk dönemindeki çocukların akran oyun davranışlarının niteliğinin değerlendirilmesi için tasarlanmış, Ahmetoğlu, Acar ve Aral (2016) tarafından Türkçe uyarlaması ve geçerlik-güvenirliği yapılmış olan “Penn Etkileşimli Akran Oyun Ölçeği-Ebeveyn Formu” kullanılarak elde edilmiştir. Elde edilen verilerin analizinde betimsel istatistikler incelenmiş, varyans analizi, t-testi ve pearson momentler çarpımı korelasyon katsayısı teknikleri kullanılmıştır. Yapılan analizler sonucunda Anne ve babanın öğrenim durumu Demoulin Çocuklar için Benlik Algısı Ölçeğinin bazı alt ölçeklerinde farklılaşma yarattığı görülmüştür. Bu sonuçların aksine anne ve babanın öğrenim durumu maddesinin benlik algısı üzerinde farklılaşma yaratmadığı sonucu çıkmıştır. Aynı şekilde kardeş sayısı da benlik algısı üzerinde herhangi bir farklılık yaratmamıştır. Benzer şekilde, ailelerin sosyo-ekonomik düzeyleri de benlik algısı üzerinde herhangi bir farklılık yaratmamıştır. Araştırmadan elde edilen bulgular ilgili literatür ışığında tartışılmış; araştırmacılara, öğretmenlere ve ailelere yönelik önerilerde bulunulmuştur.

The aim of this study is to examine the relationship between the self-perceptions and interactive play behaviors of children aged 48-72 months attending preschool education institutions, considering various variables. The research was planned and conducted according to the relational screening model. The study group consists of a total of 300 children aged 48-72 months who are attending preschool education institutions affiliated with the Ministry of National Education in the central districts of Gaziantep and were selected by random sampling. The research was planned and carried out according to the relational screening model. The study group of the research consists of a total of 300 children aged 48-72 months, who attend pre-school education institutions affiliated with the Ministry of National Education in the central districts of Gaziantep province and were selected by random sampling method. Data of the research; Personal information form containing demographic information, Dr. The Demoulin Self-Perception Scale for Children, which was developed by Donald DeMoulin between 1995 and 1998 and was translated into Turkish by Zembat et al. (2016) and its validity and reliability were established, and Fantuzzo, Mendez and Tighe (1998) used it to determine the peer play behaviors of children in early childhood. It was obtained using the Penn Interactive Peer Play Scale-Parent Form, which was designed to evaluate the quality of the game and was adapted into Turkish and its validity and reliability were made by Ahmetoğlu, Acar and Aral (2016). In the analysis of the data obtained, descriptive statistics were examined, analysis of variance, t-test and Pearson product moment correlation coefficient techniques were used. As a result of the analysis, it was seen that the educational status of the mother and father created a difference in some subscales of the Demoulin Self-Perception Scale for Children. Contrary to these results, it was concluded that the item on the educational status of the mother and father did not create a difference in the self-perception. Likewise, the number of siblings did not make any difference on self-perception. Similarly, the socio-economic levels of families did not make any difference on self-perception. The findings obtained from the research were discussed in the light of the relevant literature; Suggestions were made for researchers, teachers and families.
Examining the relationship between preschool children's interactive play behaviors and self-perception
Keywords: Benlik Algısı Preschool Education; Education, Preschool; Eğitim, Okul öncesi; Etkileşimli Oyunlar; Interactive Play; Okul Öncesi Eğitim; Okul öncesi öğretim; Preschool teaching; Self-Perception